First-principles study of C cites vacancy defects in water adsorbed Graphene - Neupane, Hari Krishna; Adhikari, Narayan Prasad (Himalayan Physics, 2020)
The electronic and magnetic properties of water adsorbed graphene (wad – G), single carbon (1C) atom vacancy defects in water adsorbed graphene (1Catom-vacancy – wad – G) and double carbon (2C) atoms vacancy defects in water adsorbed graphene (2Catom-vacancy – wad – G) materials are studied by ﬁrst-principles calculations within the frame work of density functional theory (DFT) using computational tool Quantum ESPRESSO (QE) code. We have calculated the binding energy of wad – G, 1Catom-vacancy – wad – G and 2Catom-vacancy – wad – G materials, and then found that non-defects geometry is more compact than vacancy defects geometries. From band structure calculations, we found that wad – G is zero band gap semiconductor, but 1Catom-vacancy – wad – G and, 2Catom-vacancy – wad – G materials have metallic properties. Hence, zero band gap semiconductor changes to metallic nature due to C sites vacancy defects in its structures. We have investigated the magnetic properties of wad – G and its C sites vacancy defects materials by using Density of States (DOS) and Partial Density of States (PDOS) calculations. We found that wad – G is non- magnetic material. 1C atom vacancy defects in graphene surface of wad – G is induced magnetization by the re-bonding of two dangling bonds and acquiring signiﬁcant magnetic moment (0.11 µB/ cell) through remaining unsaturated dangling bond. But, 2C atoms vacancy defects in graphene surface of wad – G induced low value of magnetic moment (+0.03 µB/ cell) than 1C atom vacancy defects in structure, which is due to no dangling bonds present in the structure. Therefore, non-magnetic, wad – G changes to magnetic, 1Catom-vacancy – wad – G and, 2Catom-vacancy – wad – G materials due to C sites vacancy defects in wad – G structure. The 2p orbital of carbon atoms has main contribution of magnetic moment in defects structures.